POSSIBILITY USING OF GIS TECHNOLOGY FOR THE MANAGEMENT OF WATER RESOURCES IN TAJIKISTAN (Journal of Geography and Environmental Management, 2016)
This article discusses the possibility of using GIS technology at the local level.